2020
DOI: 10.1590/s1980-220x2018058603565
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of Chagas disease and its correlation with health services

Abstract: Abstract Objective: To analyze the spatial distribution of Acute Chagas Disease (ACD) cases in a riverside municipality and make relationships with the notifying health services. Method: Longitudinal, ecological, quantitative study with use of geoprocessing techniques, conducted with cases of acute Chagas disease in the municipality of Abaetetuba/Pará. Results: Inclusion of 204 disease cases. Predominance of the male sex, mixed race and primary education as educational level. The highest incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 12 publications
1
3
0
4
Order By: Relevance
“…Studies in endemic countries have reported strong spatial associations between CD cases related to environmental factors and housing characteristics [ 16 , 40 , 41 ], whereas hospitalizations are more concentrated in capitals and larger cities where complex medical care, equipment, and specialists are more likely available. This phenomenon has been consistently observed in other CD endemic countries such as Bolivia and Brazil [ 16 , 42 , 43 ]. On the other hand, individuals from socially disadvantaged backgrounds and rural origins, who already face challenges in health care access in general, encounter additional difficulties in accessing hospitals.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Studies in endemic countries have reported strong spatial associations between CD cases related to environmental factors and housing characteristics [ 16 , 40 , 41 ], whereas hospitalizations are more concentrated in capitals and larger cities where complex medical care, equipment, and specialists are more likely available. This phenomenon has been consistently observed in other CD endemic countries such as Bolivia and Brazil [ 16 , 42 , 43 ]. On the other hand, individuals from socially disadvantaged backgrounds and rural origins, who already face challenges in health care access in general, encounter additional difficulties in accessing hospitals.…”
Section: Discussionsupporting
confidence: 68%
“…Sex was not associated with hospitalization diagnosis. However, previous national and international literature has shown that severity and mortality are significantly higher in men [ 13 , 40 , 42 ]. The higher prevalence and severe manifestations in men have been attributable to greater exposure due to mobility and circulation in places that favor T .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dessa forma, o acesso limitado ao conhecimento científico e a baixa escolaridade contribuem para que os indivíduos careçam de informações acerca de medidas profiláticas e do melhor tratamento a ser buscado em casos de contaminação, bem como do acompanhamento médico posterior, a fim de se evitar maiores complicações ou sequelas da DC (SOUSA et al, 2020). Todos esses pontos são fatores epidemiológicos que contribuem para a proliferação dos vetores e para a propagação da DC (NIELEBOCK et al, 2020;SANTANA et al, 2020;CARDOSO et al, 2020;SANTOS et al, 2020;SOUSA et al, 2020;FIDALGO et al, 2021).…”
Section: Região E Etniaunclassified
“…Segundo o Instituto Brasileiro de Geografia e Estatística, mais da metade dos nordestinos e dos nortistas são pardos (IBGE, 2019). Diante disso, tem-se que a população acometida com a Doença de Chagas está intrinsecamente ligada à etnia majoritária das populações dessas regiões que, juntas, somam quase que a totalidade dos casos registrados de transmissão por Trypanosoma cruzi entre os anos de 2011 e 2020 no Brasil (LIDANI et al, 2020;SANTOS et al, 2020;SOUSA et al, 2020;GÓES et al, 2020;CARDOSO et al, 2020;ARRUDA et al, 2019).…”
Section: Região E Etniaunclassified